Answer:
Proof for ![k|r](https://tex.z-dn.net/?f=k%7Cr)
Step-by-step explanation:
We are given that a, n, b, r and k are integers.
Also,
![a = nb + r](https://tex.z-dn.net/?f=a%20%3D%20nb%20%2B%20r)
Since k divides a and b, we can write,
a = rk and b = sk, where r and s are integers.
Now, we have to prove that k divides r as well that is ![k|r](https://tex.z-dn.net/?f=k%7Cr)
Putting value of a and b in the equation, we get:
![rk = n(sk) + r\\r = rk - nsk\\r = (r-sn)k](https://tex.z-dn.net/?f=rk%20%3D%20n%28sk%29%20%2B%20r%5C%5Cr%20%3D%20rk%20-%20nsk%5C%5Cr%20%3D%20%28r-sn%29k)
Since, (r-sn) is an integer, k divides r.